2017
DOI: 10.3390/polym9120714
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Stretchable Piezoelectric Nanogenerators via Large-Scale Aligned Fractal Inspired Micro/Nanofibers

Abstract: Stretchable nanogenerators that directly generate electricity are promising for a wide range of applications in wearable electronics. However, the stretchability of the devices has been a long-standing challenge. Here we present a newly-designed ultra-stretchable nanogenerator based on fractal-inspired piezoelectric nanofibers and liquid metal electrodes that can withstand strain as large as 200%. The large-scale fractal poly(vinylidene fluoride) (PVDF) micro/nanofibers are fabricated by combination of helix e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…For the linear photoresist pattern, a short nozzle‐to‐substrate distance (H) is used to improve positioning via a high‐speed moving stage and avoid the influence of spiraling phenomenon . Oppositely, the “whipping/buckling” phenomenon of the electrospinning jet is used to directly fabricate serpentine pattern with diverse geometries in a programmable, accurately positioned, and individually controlled manner. When the substrate speed (V) gradually decrease and not enough to neutralize the spiraling speed of the photoresist jet, the spiraling jet can print serpentine pattern on the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…For the linear photoresist pattern, a short nozzle‐to‐substrate distance (H) is used to improve positioning via a high‐speed moving stage and avoid the influence of spiraling phenomenon . Oppositely, the “whipping/buckling” phenomenon of the electrospinning jet is used to directly fabricate serpentine pattern with diverse geometries in a programmable, accurately positioned, and individually controlled manner. When the substrate speed (V) gradually decrease and not enough to neutralize the spiraling speed of the photoresist jet, the spiraling jet can print serpentine pattern on the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, various portable smart devices are playing major roles in daily life, and these devices require lighter, smaller, or larger capacity power sources. Related research topics such as sensors [9,10], energy harvesting [11][12][13][14], piezoelectric nanogenerators (PENGs) [15][16][17], and triboelectric nanogenerators (TENGs) have received significant attention [18][19][20][21][22][23] because a large amount of available energy is generated by the human movement and clothing friction. The triboelectric effect is caused by the contact between different materials, and it can induce strong electrostatic charges.…”
Section: Introductionmentioning
confidence: 99%
“…Since the fiber-based TENG was introduced by Zhong et al in 2014 [35], related studies have been actively reported [15,16,36]. Notably, the TENG using nanofibers has been widely investigated because of its advantages, such as ease of production by electrospinning and high surface roughness [37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Various kinds of technologies, such as piezoelectric, triboelectric, electromagnetic, and pyroelectric have been considered and studied. Among these self‐powered technologies, piezoelectric generators have proven to be a great candidate as energy harvesters for skin‐integrated or even biointegrated electronics, due to the combination of their excellent electrical properties and advanced mechanical designs . Materials and mechanical engineering in piezoelectric materials, including lead zirconate tinanate (PZT), PVDF, BaTiO 3 , NaNbO 3 , and ZnO have been made great progress and realized outstanding electromechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Among these self‐powered technologies, piezoelectric generators have proven to be a great candidate as energy harvesters for skin‐integrated or even biointegrated electronics, due to the combination of their excellent electrical properties and advanced mechanical designs . Materials and mechanical engineering in piezoelectric materials, including lead zirconate tinanate (PZT), PVDF, BaTiO 3 , NaNbO 3 , and ZnO have been made great progress and realized outstanding electromechanical properties. However, complicated fabrication processes involving high temperature deposition, multiple steps photolithographs, physical/chemical etchings, and transfer printings are typically needed to meet the requirement of flexibility …”
Section: Introductionmentioning
confidence: 99%